Productivity, soil fertility and economic viability of fodder tree–crop silvipastoral systems in southern Karnataka, India - M. Harshitha; D. C. Hanumanthappa; A. R. Ravi; Gaddam Sudharshan Redday; Abhishek Godi (Agroforestry Systems, 2026)

First report of DMI and QoI fungicides resistance in Erysiphe necator in the Karnataka state in India - N. Sagar; M. M. Jamadar; M. K. Sunil; T. Sushma; K. N. Pallavi; J. Sneha; C. Harshitha (European Journal of Plant Pathology, 2025)

Fatigue performance and thickness optimization of polyolefin fiber-reinforced M40 concrete for sustainable pavements - J. C Vidyashree; E. K Reshma; M. Harshitha; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2025)
Concrete pavements are renowned for their ability to handle heavier loads and lower life cycle costs than flexible pavements. Fibers into concrete further enhance its durability by reducing maintenance and rehabilitation costs. This study investigates the fatigue performance of pavement quality concrete (PQC) M40-grade reinforced with polyolefin fibers, focusing on structured fibers (SF) and twisted fibers (TF). Polyolefin fibers were added at varying dosages (0.8, 0.9, and 1.0 kg/m³ for structured fibers and 3, 4, and 5 kg/m³ for twisted fibers), as per IRC: 44 (2017) guidelines. Tests were conducted for compressive, split tensile, flexural strength, and flexural fatigue under different stress levels and loading frequencies. Results revealed that polyolefin fibers significantly improve concrete’s mechanical properties and fatigue resistance. Optimal dosages were identified as 1 kg/m³ for structured fibers and 5 kg/m³ for twisted fibers. The S-N curves demonstrated enhanced durability under cyclic loading conditions. Furthermore, polyolefin fiber reinforcement reduced white topping thickness from 19 cm to 17 cm while maintaining flexural stress within safe limits. This optimization highlights the potential for more durable, cost-effective, and sustainable pavement solutions.

Spatio-temporal tectonic progression in the Dharwar Craton: Insights from volcanic records of Archean greenstone belts - G. Harshitha; Jayant K Yadav; C. Manikyamba; M. Santosh; Li Tang; K.S.V. Subramanyam (Precambrian Research, 2025)

Anthocyanins of Delonix Regia Floral Petals: A Novel Approach on Fluorescence Enhancement, Forster Resonance Energy Transfer Mechanism and Photostability Studies for Optoelectronic Applications - D. Harshitha; Anil Kumar; H. M. Mahesh; C. G. Renuka (Journal of Fluorescence, 2024)

Study on the anatomy of the pink mealybug Maconellicoccus hirsutus (Hemiptera: Pseudococcidae) using stereo microscopy - Channabasava Veershetty; Harshitha Prakash; Pawan Shukla; Kangayam M. Ponnuvel (International Journal of Tropical Insect Science, 2023)

TP53 codon 72 polymorphism and type 2 diabetes: a case–control study in South Indian population - Harshitha K. Punja; Dechamma Pandyanda Nanjappa; Nishith Babu; Krithika Kalladka; B. Shanti Priya Dias; Gunimala Chakraborty; Sudhindra M. Rao; Anirban Chakraborty (Molecular Biology Reports, 2021)

Effect of rs11614913 Polymorphism on Mature miR196a2 Expression and its Target Gene HOXC8 Expression in Human Glioma - M K Sibin; S M Harshitha; K V L Narasingarao; I Bhat Dhananjaya; P Shukla Dhaval; G K Chetan (Journal of Molecular Neuroscience, 2017)